EPC Agenda 2005-04-28 - Academic Senate:::::::::
Educational Policies Committee. Special Student Report. Chair Report. Agenda amended and approved. Minutes of 3/18/2021 – Approved. Consent items: THAR Concentration in Acting Revision, THAR Concentration in Technical Theatre Revision, THAR Concentration in Theatre Studies Revision, Candidates for Graduation – Approved. Motion that the Academic Senate endorse the EPC statement on administrative encroachment into curricular matters – Endorsed. President Report. Provost Report. From FSAC: Revision to the RTP policy – First Reading completed. Posthumous Degree request for Lisa Dunwoody – Approved. FSAC Report. From EPC: Discontinuance of Dance concentration in THAR – First Reading completed. Vice President of Administration and Finance Report. From EPC: Request for Waiver of A3 for Engineering program – Second Reading. Vice President for Student Affairs Report. Statewide Senator Report. Good of the Order.